Finding justice in wild, novel ecosystems: a review through a multispecies lens - Collier, Marcus (My University, 2023)
Mainstreaming nature-based solutions in cities has grown in scale and magnitude in recent times but is still considered to be the main challenge for transitioning our cities and their communities to be more climate resilient and liveable: environmentally, economically, and socially. Furthermore, taking nature-based solutions to the next level, and scaling them out to all urban contexts to achieve a greater impact, is proving to be slow and often conflicts with other transitioning initiatives such as energy generation, mobility and transport initiatives, and infilling to combat sprawl. So, the task is neither easy nor straightforward; there are many barriers to this novel transition, especially when it comes to collaborative approaches to implementing nature-based solutions with diverse urban communities and within city authorities themselves. This paper reports on a new process that is systematically co-produced and captured as a framework for planning nature-based solutions that emerged during the Connecting Nature project. The Connecting Nature Framework is a three-stage, iterative process that involves seven key activity areas for mainstreaming nature-based solutions: technical solutions, governance, financing and business models, nature-based enterprises, co-production, reflexive monitoring, and impact assessment. The tested and applied framework is designed to address and overcome barriers to the implementation of nature-based solutions in cities via a co-created, iterative, and reflective approach. The planning process guided by the proposed framework has already yielded promising results with some of the cities of the project, though further usage and its adoption by other cities is needed to explore its potential in different contexts especially in the Global South. The paper concludes with suggestions on how this may be realised.
PUBLISHED
Though most cities, particularly in the Global North, have been intensely modified by human activities certain locations still exist in varied forms of abandonment or disinvestment, often allowing for new species assemblages to flourish. These urban novel ecosystems or informal wild spaces are often perceived as in-between or overlooked, calling into question their value and social-ecological role, while also creating tensions amongst different groups and stakeholders who share different visions for their use and management. Within these tensions, issues of justice and equity can be more pronounced and surface historic legacies of environmental contamination, inequitable development, and extraction. Despite this, very little is known about the social-ecological role informal wild spaces play in urban areas, and how best to interrogate and understand the equity and justice dimensions they elicit. To fill this gap in knowledge, this paper critically examines the literature on urban novel ecosystems in relation to justice, with a particular interest in multispecies justice. Through this analysis, gaps in the literature are exposed, while also arguing the informality, neglect and contestation of wild urban spaces provides opportunities to explore issues of access, benefits and harms, particularly in light of global climate and ecological crises. A systematic approach is utilized to search the literature, identifying 45 papers which are thematically analyzed under a justice lens. The study identifies three themes that thread throughout the literature: distributional injustices relate to perceptions and attitudes, which give rise or arise from injustices; the regeneration discourse focuses on a new nature, which is based on social-ecological displacement and devaluation; and the potential of urban wild spaces to generate new multispecies sensibilities. The paper concludes by discussing trends, gaps, and emerging discourses, and proposing a multispecies justice approach for urban planning through the learnings and engagement with urban wild, novel ecosystems.
Keywords: Novel ecosystems; Informal wild spaces; Justice; Cities; Systematic review; Identities in Transformation; International Development; International Integration; Smart & Sustainable Planet; CITIES; Climate Justice; E3; Informal wild spaces; Justice; NOVEL ECOSYSTEMS; Nature Positive Economy; NovelEco; REWILDING; SYSTEMATIC REVIEW; Attitudes; Development; Environment and housing; Policy; Social exclusion; Social participation